Teaching and transitions: understanding classroom practices that support higher education progression in England. Issue 2 (3rd April 2021) - Raven, Neil
ABSTRACT: Teachers are often portrayed as the recipients of information about widening access initiatives and cast in the role of encouraging their students to engage in these activities. However, recent research has corroborated what might constitute an expected association, given the time pupils spend at school: teachers can have a significant impact on the higher education [HE] intentions of young people. Yet, few studies have considered the classroom practices that may account for this. This study seeks to do this by drawing on the insights and experiences of students and teaching professionals based in two schools and a post-16 college. All three institutions have catchments that encompass educationally deprived neighbourhoods. What this investigation reveals is that certain practices can make a significant difference to educational ambitions. Prominent are those that nurture subject interest, link the school curriculum to HE options, and introduce learners to higher-level study skills. In turn, the effectiveness of these practices is influenced by the ability of teaching professionals to build rapport with their students, most prominently by sharing their own learner journeys. The paper concludes by arguing for the wider recognition of these practices since they have the potential to open up HE to more young people from backgrounds that are underrepresented in HE.